The Role of Inositol in Thyroid Physiology and in Subclinical Hypothyroidism Management - Benvenga, Salvatore; Nordio, Maurizio; Laganà, Antonio Simone; Unfer, Vittorio (Frontiers in Endocrinology, 2021)
Myo-Inositol (MYO) is the most abundant stereoisomer of inositols’ family, cyclic polyols with 6 hydroxyl groups. Myo-Inositol has a relevant role in thyroid function and autoimmune diseases, as a precursor of phosphoinositides that takes part in the phosphatidylinositol (PtdIns) signal transduction pathway. Among phosphoinositides, phosphatidylinositol 4,5- bisphosphate (PIP2) is the precursor of inositol triphosphates (IP3), second messenger of several hormones including thyroid-stimulating hormone (TSH). As a second messenger in the phospholipase C (PLC)-dependent inositol phosphate Ca2+/DAG pathway, Myo-Inositol is essential to produce H2O2 required for the synthesis of thyroid hormones. Consequently, depletion of Myo-Inositol or impaired inositol dependent TSH signaling pathway may predispose to the development of some thyroid diseases, such as hypothyroidism. Many clinical studies have shown that after treatment with Myo-Inositol plus Selenium (MYO + Se), TSH levels significantly decreased in patients with subclinical hypothyroidism with or without autoimmune thyroiditis. The TSH reduction was accompanied by a decline of antithyroid autoantibodies. Moreover, Myo-Inositol supplementation seemed to be involved also in the management of thyroidal benign nodules, with a possible effect in the size reduction. This review proposes a summary of the role of inositol, especially of Myo-Inositol, in the thyroidal physiology and its contribution on the management of some thyroid diseases.